White Evangelicals, White Supremacy, and the ‘Born Again’ Identity in a Post-Trump America A Latino Reading of John 3:1–8 - Galvan Estrada, Rodolfo (2022)
This essay seeks to provide a Latino rereading of the ‘born again’ identity in John 3:1–8. It argues that being ‘born again’ is not a religious identity as popularly understood in American evangelicalism but an anti-racist identity that rejects all notions of racial superiority through the negation of birthing privileges. To champion or support racist policies toward Latin American migrants (or any minoritized community) is contrary to the very identity of a ‘born again’ believer. This Latino reading explores the racial context of the historical milieu of the New Testament and reflects upon the contemporary challenges of white supremacy and white evangelicalism in a post-Trump America.